Hurtownie materiału dydaktycznego w systemie nauczania wirtualnego - Nycz, Małgorzata (The didactic materials warehouses in virtual education system, 2005)
Virtual education is one of the features of information society. The quality of didactic process depends on quality of knowledge collected within the system. This aspect is especially important in virtual education system. The paper presents the idea of the didactic materials warehouse within the education system.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 199-208